The Influence of Small Clear-Distance Tunnel Construction on Adjacent High-Voltage Transmission Tower Foundation - Aijun Yao; Jinbiao Lin; Bin Ren (Advances in Civil Engineering)
The new tunnel construction will inevitably cause the change of the stress field and displacement field of the stratum where the adjacent existing structures are located, which poses a great threat to the safe and stable operation of the existing structures. Reasonable selection and optimization of construction sequence and construction method of double tunnels with small clear distance are of great significance to the safe and stable operation of existing structures. In this present study, taking the Xiaohan municipal double-arch highway tunnel near the high-voltage transmission tower as the engineering background, the ABQUS finite element numerical simulation method is used to analyze the influence of tunnel construction on the existing high voltage tower foundation. The accuracy of the numerical method is verified compared with the theoretical solution of induced stress at the bottom of the tower foundation caused by the excavation of circular cavity. Then, the influence law of tunnel position on induced stress field is discussed by parameter analysis. On this basis, the construction sequence which has the least influence on the tower foundation is selected by comparing the numerical simulation results of different construction schemes. That is, the left tunnel shall be excavated after the construction of the right tunnel is completed. Finally, the change of the settlement of the existing tower foundation, the stress of the base, and the inclination degree during the CD method excavation is analyzed. The results show that simultaneous excavation of new tunnels has the greatest influence on the settlement and stress increment of the existing tower foundation. It provides suggestions to construct the double tunnels step by step from far side to near side in similar projects.